Conducting systematic literature reviews and bibliometric analyses. Issue 2 (May 2020) - Linnenluecke, Martina K; Marrone, Mauricio; Singh, Abhay K
Literature reviews play an essential role in academic research to gather existing knowledge and to examine the state of a field. However, researchers in business, management and related disciplines continue to rely on cursory and narrative reviews that lack a systematic investigation of the literature. This article details methodological steps for conducting literature reviews in a replicable and scientific fashion. This article also discusses bibliographic mapping approaches to visualise bibliometric information and findings from a systematic literature review. We hope that the insights provided in this article are useful for researchers at different stages of their careers – ranging from doctoral students who wish to assemble a broad overview of their field of interest to guide their work, to senior researchers who wish to publish authoritative literature reviews. JEL Classification:C18, C80, C88, M10, M20